Epigenetics of Colorectal Cancer - Goel, Ajay (2012)
In the early years of the molecular biology revolution, cancer research was mainly focused on genetic changes (ie, those that altered DNA sequences). Although this has been extremely useful as our understanding of the pathogenesis and biology of cancer has grown and matured, there is another realm in tumor development that does not involve changing the sequence of cellular DNA. This field is called “epigenetics” and broadly encompasses changes in the methylation of cytosines in DNA, changes in histone and chromatin structure, and alterations in the expression of microRNAs, which control the stability of many messenger RNAs and serve as “master regulators” of gene expression. This review focuses on the epigenetics of colorectal cancer and illustrates the impact epigenetics has had on this field.